2018
DOI: 10.3389/fcimb.2018.00109
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Two Human ATG10 Isoforms on Replication of a HCV Sub-genomic Replicon Are Mediated via Regulating Autophagy Flux in Zebrafish

Abstract: Autophagy is a host mechanism for cellular homeostatic control. Intracellular stresses are symptoms of, and responses to, dysregulation of the physiological environment of the cell. Alternative gene transcription splicing is a mechanism potentially used by a host to respond to physiological or pathological challenges. Here, we aimed to confirm opposite effects of two isoforms of the human autophagy-related protein ATG10 on an HCV subgenomic replicon in zebrafish. A liver-specific HCV subreplicon model was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The decreased protein levels of ATG10 long isoform in ATG10 rs1864182G carriers were associated with the reduction of autophagic flux, its canonical function, in agreement with previous observations [ 21 ]. Given the role of autophagy in leukemia [ 52 ], and in chemotherapy susceptibility and resistance [ 53 , 54 , 55 ], this reduction in autophagy could potentially be beneficial to lower the probability of developing AML.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The decreased protein levels of ATG10 long isoform in ATG10 rs1864182G carriers were associated with the reduction of autophagic flux, its canonical function, in agreement with previous observations [ 21 ]. Given the role of autophagy in leukemia [ 52 ], and in chemotherapy susceptibility and resistance [ 53 , 54 , 55 ], this reduction in autophagy could potentially be beneficial to lower the probability of developing AML.…”
Section: Discussionsupporting
confidence: 92%
“…We next evaluated the protein levels of the ATG10 long isoform, which is mainly involved in autophagy catalytic function [ 21 , 22 ]. In the presence of the ATG10 rs1864182G , a statistically significant decrease of 25% in the ATG10 long isoform levels was observed ( Figure 1 G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased numbers of autophagosomes can be due to an increase in the formation of autophagosomes or a reduction in autophagosome turnover caused by late suppression of autophagy. We confirmed that BBR impaired autophagy by monitoring the process of autophagic flux in the presence of autophagy inhibitors chloroquine (CQ) and 3-methyladenine (3-MA) [ 31 ] in GFP-LC3B LX2 cells (Supplementary Fig. 5A–H ).…”
Section: Resultsmentioning
confidence: 68%